Exploring Teachers’ Use of First Language (L1) in EFL Classroom - Elisabeth Marsella (TEKNOSASTIK, 2020)
Teachers are always seen as the role model of the classroom. Students tend to imitate what the teachers speak and do, including in English classroom. It has been popular that in English classroom teachers impose the students to use English (L2) only. However, the practice showed that teachers still use L1 in their teaching. Regarding that fact, this study aims to investigate how teachers use first language (L1) in English classroom. The study involves experienced teachers from two private schools in Bekasi, a junior high school and a senior high school. Observations, video and audio recording, and interview were conducted to collect the data. From the data, it is obtained the teacher talk (TT) where the teachers mostly used English. Although the teachers used English and encouraged students to use English, it turned out that in some situation L1 is unavoidable. The teachers used L1 during the class learning. This teachers’ L1 was then analyzed from the perspective of initiation, response, feedback (IRF) exchange. The result shows that teachers performed typical acts and functions in the class interaction. Moreover, teachers’ L1 was not necessarily showing incompetence or reluctance to use L2. Rather, L1 use performed functions in the classroom that it helped teachers build students’ knowledge and manage the class more efficiently.